Description of the Way of Preaching Rasulullah saw. in the Book of History of Islamic Culture (SKI) in Grade 4 Madrasah Ibtidaiyah (MI) Level - Abdul Gani Jamora Nasution; Dinah Nadhifah; Arfatussalamah Tanjung; Pipi Andriani (Journal of Contemporary Islamic Primary Education, 2022)
This study aims to describe the way of preaching the Prophet Muhammad. in the SKI book at class 4 MI level. The type of research used in this research is in the form of library research. The object of study in this study uses reading books and journals that are relevant to the preaching of Rasulullah SAW. The results of the study found discussions in textbooks, namely: (1) Sirriyah Da'wah (secret), Dakwah which was carried out to the closest people such as family, relatives and friends in a clandestine manner. (2) Blatant Da'wah, Da'wah that is carried out openly. (3) The Prophet's Challenges and Fortitude in Preaching. Based on the results of this study, it can be concluded that the author in the SKI text book conveys in the form of questions what can be emulated from the Prophet's da'wah. So that students can express and imitate some of the Prophet's examples after hearing stories from educators about the Prophet's journey in preaching. This can stimulate students to be active in learning.